A migração fractal do provérbio: práticas, sujeitos e narrativas entrelaçadas - Paxe, Abreu Castelo Vieira dos (2016)
This research proposes to investigate the translations between textualities of the proverb from the Angolan and African contexts and discourses that these ones cross: from a model of experimentation of avant-garde art that mix between chromaticism and sounds to the graphicvisual forms. In the corpus are listed bases of these textualities of three regions: the pot script, mats, in Cabinda, northern Angola; the sand on drawings or lusona, and rock art in Lunda, east of Angola; the dances of shepherds in the southern region of Angola. These cases are analyzed from the perspective of cultural miscegenation, of baroque cultures mechanisms in Africa and how assumptions of border cultures. The narratives in vehicles of different media are examined taking for granted the assumption the hypothesis that the images and textualities are constantly created, recreated and updated by each other, with this vehicle to take up the role of traditional artistic forms with intersecting forms. As Amalio Pinheiro, this circularity is treated by zigzags in reframing of cultural elements, being Africa the place of miscegenation and intersecting par excellence. Investigate these media-art procedures noncanonical from primitive realities also means understanding the processes of abstraction and migration of things in relation nature-human-culture-city, it sets the fictionalization of the life and textualization of quotidian elements. Ana Hatherly speaks of the need to reconnection between people and the tradition, which it can be dynamic. To some extent, these media practices carried out by the proverb suggests to reformulate the social reality with reallocations and changes of power in a spectacular way and into the fantastic and fable by the hypertext formation, which is dynamic and has several meanings. The role of the media has proved preponderant as a guide for these elaborations. But it is precisely from there that the problem this study arose: what are the translations undertaken for the media used by the proverb also converted on the way to the various textualities? This work is linked to the study of culture and media environments and their methodology is based on immersion in printed and oral literature through collected documents and meetings with popular storytellers and professionals who are involved in this important episode of the culture. This research revealed the expanded notion of proverb in the cultural tissue